IMPACT OF PROSTHODONTIC TREATMENT ON THE ORAL HEALTH RELATED QUALITY OF LIFE IN A MAXILLECTOMY PATIENT WITH MULTIPLE IMPAIRMENTS - Faheemuddin, Muhammad; Yazdanie, Nazia; Nawaz, Muhammad Sohaib (Journal of Ayub Medical College Abbottabad, 2014)
Oral Health Related Quality of Life is an important component in the treatment of a patient. Patients with multiple impairments have a compromised quality of life, which is further worsened by ablative maxillary surgery. A properly made oral prosthesis aids in the daily life functions and therefore, has a positive impact on the quality of life of the patient. This article discusses a case in which prosthodontic treatment improved the Oral Health Related Quality of Life in a maxillectomy patient having multiple impairments. Keywords: Quality of life, Oral Health Related Quality of Life, maxillectomy, multiple impairments, palatal obturator